The scum villain's self-saving system = Ren zha fanpai zijiu xitong. 4 - Moxiangtongxiu (Scum Villian's Self-Saving System, 2022)
[MISSION OBJECTIVE: SURVIVE] What happens after an epic tale ends? This collection of eleven short stories picks up days after Scum Villain's finale and follows the cast's relationships and adventures through their pasts and futures. The first trial? A glimpse into another world, where Luo Binghe was never saved by his beloved teacher--unless he can claim this world's Shen Qingqiu for himself. Other tales recount the riotous history of Shang Qinghua and Mobei-Jun, the bittersweet romance of Luo Binghe's parents, and the untold tragedy of the original scum villain himself.